Failures of Large Banks: Implications for Banking Supervision and Deposit Insurance - Horvitz, Paul M. (Journal of Financial and Quantitative Analysis, 1975)
Paul M. Horvitz, Failures of Large Banks: Implications for Banking Supervision and Deposit Insurance, The Journal of Financial and Quantitative Analysis, Vol. 10, No. 4, 1975 Proceedings (Nov., 1975), pp. 589-601